Simultaneously Cationic and Anionic Dyes Elimination via Magnetic Hydrochar Prepared from Copper Slag and Pinewood Sawdust - Wang, Huabin; Wu, Yi; Wen, Yi; Chen, Dingxiang; Pu, Jiang; Ding, Yu; Kong, Sailian; Wang, Shuaibing; Xu, Rui (Toxics (Basel), 2023)
In practical wastewater, cationic and anionic dyes usually coexist, while synergistic removal of these pollutants is difficult due to their relatively opposite properties. In this work, copper slag (CS) modified hydrochar (CSHC) was designed as functional material by the one-pot method. Based on characterizations, the Fe species in CS can be converted to zero-valent iron and loaded onto a hydrochar substrate. The CSHC exhibited efficient removal rates for both cationic dyes (methylene blue, MB) and anionic dyes (methyl orange, MO), with a maximum capacity of 278.21 and 357.02 mg·g−1, respectively, which was significantly higher than that of unmodified ones. The surface interactions of MB and MO between CSHC were mimicked by the Langmuir model and the pseudo-second-order model. In addition, the magnetic properties of CSHC were also observed, and the good magnetic properties enabled the adsorbent to be quickly separated from the solution with the help of magnets. The adsorption mechanisms include pore filling, complexation, precipitation, and electrostatic attraction. Moreover, the recycling experiments demonstrated the potential regenerative performance of CSHC. All these results shed light on the co-removal of cationic and anionic contaminates via these industrial by-products derived from environmental remediation materials.